2005
DOI: 10.1017/s1481803500013063
|View full text |Cite
|
Sign up to set email alerts
|

Patients who leave the emergency department without being seen by a physician: a control-matched study

Abstract: Objective: To describe the socio-demographic characteristics and clinical outcomes of patients who leave the emergency department (ED) without being seen by a physician. Methods: This 3-month prospective study was conducted at a downtown Toronto teaching hospital. Patients who left the ED without being seen (LWBS) were matched with controls based on registration time and triage level. Subjects and controls were interviewed by telephone within 1 week after leaving the ED. Results: During the study period, 386 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 23 publications
7
40
2
2
Order By: Relevance
“…The absence of death or suicide attempts among the study participants is concordant with a literature review revealing only one case of suicide attempt in a prospective study of adult patients who LWBS. 19 Finally, our results are in agreement with a 20 We used a broad definition of an unfavourable outcome, including children who only needed an intravenous access or a delayed casting. Many unfavourable outcomes were more of a delay in treatment and diagnosis as opposed to an adverse event per se.…”
Section: Discussionsupporting
confidence: 86%
“…The absence of death or suicide attempts among the study participants is concordant with a literature review revealing only one case of suicide attempt in a prospective study of adult patients who LWBS. 19 Finally, our results are in agreement with a 20 We used a broad definition of an unfavourable outcome, including children who only needed an intravenous access or a delayed casting. Many unfavourable outcomes were more of a delay in treatment and diagnosis as opposed to an adverse event per se.…”
Section: Discussionsupporting
confidence: 86%
“…9,10 Patients who leave the ED without being seen are equally likely as those who were assessed and treated to seek follow-up care. 11 Our study found no difference in T 1 or total LOS between PGY-1 and PGY-2 residents. The family medicine residency program in Canada is two years long.…”
Section: Discussioncontrasting
confidence: 62%
“…1,14,21,[23][24][25] These data are concerning because the patients who tend to LWBS are more likely to lack access to alternative primary care and be more at risk for adverse events. 3,[24][25][26] This population may be using the ED as a source of primary care, given the finding that most LWBS visits are of low acuity. On the other hand, a significant percentage of LWBS patients (26%) do have private insurance.…”
Section: Discussionmentioning
confidence: 99%